2016
DOI: 10.1186/s12867-016-0077-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel insight into the composition of human single-stranded DNA-binding protein 1 (hSSB1)-containing protein complexes

Abstract: BackgroundSingle-stranded DNA-binding proteins are essential cellular components required for the protection, metabolism and processing of single-stranded DNA. Human single-stranded DNA-binding protein 1 (hSSB1) is one such protein, with described roles in genome stability maintenance and transcriptional regulation. As yet, however, the mechanisms through which hSSB1 functions and the binding partners with which it interacts remain poorly understood.ResultsIn this work, hSSB1 was immunoprecipitated from cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
(46 reference statements)
0
12
1
Order By: Relevance
“…Recently, the Richard laboratory found that hNABP2 is associated with a large number of proteins with roles in mRNA metabolism and various chromatin-remodeling complexes [ 33 ]. Similarly, our co-IP experiment also revealed many transcription-related proteins associate with hNABP2, indicating its potential role in transcriptional regulation (Supplementary Figure S9 and Table S5).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Richard laboratory found that hNABP2 is associated with a large number of proteins with roles in mRNA metabolism and various chromatin-remodeling complexes [ 33 ]. Similarly, our co-IP experiment also revealed many transcription-related proteins associate with hNABP2, indicating its potential role in transcriptional regulation (Supplementary Figure S9 and Table S5).…”
Section: Discussionmentioning
confidence: 99%
“…hSSB1 and hSSB2 can each interact with an integrator complex subunit 3 (INTS3) and C90ORF80 to form trimeric SS binding complexes termed SOSS1/2 (sensors of single stranded DNA) complexes [79] (Figure 4). In addition to complexation with the INTS3 and C9orf80, hSSB1 forms protein-protein interactions with NBS1, a component of the MRE11-RAD50-NBS1 (MRN) repair complex that was recently shown to be regulated by SUMOylation [80,81]. Depletion of hSSB1 inhibited MRN recruitment to sites of DSB and diminishes MRN nuclease activity.…”
Section: Hssb1/2mentioning
confidence: 99%
“…In addition to their role in coating and protecting lagging strand DNA, they are necessary for protection of single-stranded regions generated during other processes, including restarting stalled replication forks, homologous recombination, and DNA repair [ 1 , 2 , 3 , 4 ]. During these processes, SSB/RPA proteins recruit and interact with a variety of other cellular proteins, and their interactions change depending on the state of the DNA [ 1 , 4 , 5 , 6 ]. Through these interactions, SSB/RPAs orchestrate the process being carried out [ 1 , 2 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…During these processes, SSB/RPA proteins recruit and interact with a variety of other cellular proteins, and their interactions change depending on the state of the DNA [ 1 , 4 , 5 , 6 ]. Through these interactions, SSB/RPAs orchestrate the process being carried out [ 1 , 2 , 4 , 5 , 6 ]. SSBs/RPAs are characterized by containing one or more ssDNA binding domains, oligonucleotide oligosaccharide-binding (OB) fold domains, and are thought to have originated from duplication of an ancestral SSB gene [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%